Analysis of Program Development, Benefits, and Challenges of Implementing "Kampus Mengajar" in Improving Teaching Skills of Muhammadiyah Makassar University Students - Rezki Ramdani; Agustan Agustan; Muthia Mutmainnah Darmuh (Journal La Edusci, 2022)
The purpose of this study is to analyse the development of the Kampus Mengajar programme and its role in improving the teaching skills of students at the University of Muhammadiyah Makassar, as well as the opportunities, benefits, and challenges of the program. This research uses a qualitative case study approach, with the participants being students of Muhammadiyah University of Makassar and the school staff, including the principal, teachers, and staff of SDI Bontoramba in Gowa Regency, South Sulawesi. The results showed that the Kampus Mengajar programme plays a very important role in developing and improving student teaching abilities and skills obtained through implemented programmes and teaching assistance in terms of increasing student literacy and numeracy. In addition, other programmes such as technology adaptation and administrative assistance also provide great benefits to the school, especially training on the implementation of online learning and the development of learning media. Teachers in the school are also able to practise directly and develop the ability to use technology in the teaching and learning process with the help of students at Kampus Mengajar. The role of universities also has a major impact on improving students' teaching abilities through evaluation and student teaching feedback. The program's challenges for students are related to a lack of student ability in terms of using technology during learning, as well as some students' low literacy and numeracy skills, requiring more intensive assistance, and also requiring creativity and innovation in creating learning media that are fun, useful, and on target.